2015
DOI: 10.1111/aas.12492
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy attenuates central sensitization induced by a thermal injury in humans

Abstract: The results indicate that HBO2 therapy in humans attenuates central sensitization induced by a thermal skin injury, compared with control. These new and original findings in humans corroborate animal experimental data. The thermal injury model may give impetus to future human neurophysiological studies exploring the central effects of hyperbaric oxygen treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 74 publications
1
36
0
Order By: Relevance
“…Several experimental studies, using different methods and treatment dosages, have shown anti-inflammatory effects of HBOT,57 but there is a paucity of studies investigating these effects in humans. A previous study,8 carried out by the present authors, was the first in humans to demonstrate an ameliorating effect of HBOT on the pathophysiological consequences following a previously validated inflammatory burn injury (BI) model 911. We demonstrated an attenuation of secondary hyperalgesia areas (SHA) in normal skin surrounding the injury, likely reflecting a central anti-nociceptive effect.…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…Several experimental studies, using different methods and treatment dosages, have shown anti-inflammatory effects of HBOT,57 but there is a paucity of studies investigating these effects in humans. A previous study,8 carried out by the present authors, was the first in humans to demonstrate an ameliorating effect of HBOT on the pathophysiological consequences following a previously validated inflammatory burn injury (BI) model 911. We demonstrated an attenuation of secondary hyperalgesia areas (SHA) in normal skin surrounding the injury, likely reflecting a central anti-nociceptive effect.…”
Section: Introductionsupporting
confidence: 50%
“…The original study was a randomized, controlled, crossover study with an open therapeutic design 8. The objective of the present study was to replicate our findings, adding an improved single-blinded design, ie, blinding for examiner bias.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The different characteristics of the punctate stimulators were chosen in order to get skin pressures just perceivable (just above detection threshold; PS1 ; Table 1), between detection and pain threshold ( PS2 ), near pain threshold ( PS3 ) and above pain threshold ( PS4 ), in hyperalgesic skin (Rasmussen et al, 2015; Ravn et al, 2013). The PS1–PS3 were polyamide monofilaments (Stoelting Europe, Dublin, Ireland; designated values 2.36, 4.93, 6.65; Table 1) while PS4 was a “weighted-pin” stimulator (MRC Systems, Heidelberg; 512 mN).…”
Section: Methodsmentioning
confidence: 99%